Jian-Pi-Yi-Shen formula restores iron metabolism from dysregulation in anemic rats with adenine-induced nephropathy. (10th August 2023) - Li, Changhui; Huang, Haipiao; Wang, Rui; Zhang, Chi; Huang, Shiying; Wu, Jinru; Mo, Pingli; Yu, Huimin; Li, Shunmin; Chen, Jianping
Abstract: Ethnopharmacological relevance: Jian-Pi-Yi-Shen (JPYS) is a herbal decoction being used to relieve the symptoms of chronic kidney disease (CKD) and its complications, including anemia, for over twenty years. Nonetheless, it is unclear how JPYS influences renal anemia and iron metabolism. Aim of the study: An analysis of network pharmacology, chemical profiling, and in vivo experiments was conducted to identify the impact of JPYS on JAK2-STAT3 pathway and iron utilization in renal anemia and CKD. Materials and methods: The chemical properties of JPYS and its exposed ingredients were detected in vivo . And based on the aforesaid chemical compounds, the potential targets and signaling pathways of JPYS for renal anemia treatment were predicted by network pharmacology. Afterward, an adenine-feeding animal model of CKD-related anemia was developed to verify the mechanism by which JPYS modulates iron recycling to treat renal anemia. Renal injury was estimated by serum creatinine (Scr), blood urea nitrogen (BUN), histopathological examinations and fibrosis degree. Western blot, enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (qPCR) and immunohistochemistry approaches were utilized to assess the levels of JAK2, STAT3 and iron metabolism-related factors. Results: There were 164 active ingredients identified in JPYS, including prototypes and metabolites in vivo were identified in JPYS, and 21 core targets were found through network pharmacology based on topological characteristics. Combined with the core targets and pathway enrichment analysis, the majority of the candidate targets were associated with the JAK2-STAT3 signaling pathways. Experimental results indicated that JPYS treatment significantly decreased the expression of BUN and Scr, restored renal pathological damage, down-regulated fibrosis degree, and improved hematological parameters such as red blood cell, hemoglobin and hematocrit in CKD rats. Furthermore, JPYS significantly restored iron metabolism from dysregulation by increasing the levels of iron and ferritin in the serum, inhibiting the production of hepcidin in liver and serum, and regulating transferrin receptor 1 in bone marrow. Meanwhile, the expression of JAK2 and STAT3 was suppressed by JPYS treatment. Conclusions: Based on these results, JPYS reduces hepcidin levels by inhibiting the activation of JAK2-STAT3 signaling, thereby protecting against iron deficiency anemia. Graphical abstract: Image 1 Highlights: 164 active ingredients identified in JPYS, including prototypes and metabolites were absorbed in vivo . Iron metabolism is the potential pathway of JPYS by network pharmacology and chemicalome-metabolome analysis. JPYS could improve renal anemia by inhibiting the activation of the JAK2-STAT3 pathway and modulating iron metabolism.